Health facilities in Seri Iskandar, Perak / Nur Alianie Rusli - Nur Alianie, Rusli (2020)
This research presents the condition and situation of health facilities in Seri Iskandar, Perak. From the initial observations, it is found that there is some issue that need to overcome such as lack of professional expertise, inadequate facilities and appliances for chronic disease. Therefore, observations were conducted and questionnaires were also distributed to get feedback from the residents of Seri Iskandar and the surrounding area. The aim is improving the existing health facilities based on residents’ comments and viewing. Based on the questionnaire distributed, it was found that most of respondent are satisfied with the available health facilities in Seri Iskandar. However, there are some concerns that have been given by the respondents. In this regard, respondents have also given recommendations and suggestions to improve health facilities in the Seri Iskandar area. Firstly, they suggest to build a hospital in Seri Iskandar, as there is no available hospital here. In addition, they also suggest to improve existing facilities and services. Other than that, the respondents recommend to employ more staff and specialist. In overall, the result of this project showed that it is highly recommended that the relevant parties need to take swift action to improve as well as strengthen health facilities in Seri Iskandar, Perak. The conclusion points to the importance of an appropriate and adequate health facilities among residents in a place, especially in Seri Iskandar, Perak.